Bioefikasi bakteri dari kulit katak sebagai agensia biokontrol terhadap penyakit antraknosa pada cabai - Lela Susilawati; P. Afrizka Sari; Maulana Septiani; E.S. Purnomo (Program Studi Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Udayana, 2023)
Amphibian skin e.g., frog carry bacterial symbionts on their skin that protect the frog from invasion of pathogen infection. This study aimed to evaluate antifungal activity of five bacterial skin frog (namely KSMD3; KSMD9; KSMD10; KSMV12; KSMV15) of Indonesian origin, Fejervarya limnocharis, against phytopathogen (Colletotrichum capsici) TCKr2. Primary screening for their antifungal activity was performed using dual culture method on nutrient agar contained 2% (w/v) of dextrose. The alteration of hyphal morphology on media and the detached chili fruit bioassay were observed. Isolate of KSMD3 was selected based on its significant performance in inhibiting the growth of the chili anthracnose pathogen, C. capsici. In addition, the KSMD3 showed low severity of disease incidence on detached chili fruit. Based on the analysis of 16S rDNA, the isolate of KSMD3 was identified as member of genera of Pseudomonas.